2022
DOI: 10.1055/a-1841-3081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Training and Taper on Neuromuscular Fatigue Profile on 100-m Swimming Performance

Abstract: This study aimed to investigate the effects of 6-week specific preparatory period and 2-week taper period on neuromuscular fatigue profile in 100-m front crawl swimming performance. Seventeen competitive-level young-adult swimmers performed a 100-m swimming performance at baseline and after 6-week specific preparatory followed by 2-week taper periods. Neuromuscular fatigue profile was assessed through percutaneous electrical stimuli on the femoral nerve during a maximal voluntary contraction performed before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…As such, the magnitude of the fatiguing effect remains similar at both time points. Combined, our findings on CMJ and race performance (mean improvement 1.7%) align well with Ribeiro et al 30 , who demonstrated that after eight weeks of training targeted specifically for a 100 m front crawl competition, performance improved by 3.06%., with post-race decreases in measures such as peak force (16.26%) and maximal voluntary contraction force (9.33%). It is noted that 2 of our participants showed large decrements in race performance, which could potentially reflect under-training, overtraining, or even a pacing strategy adopted during the heats phase of the competition.…”
Section: Discussionsupporting
confidence: 91%
“…As such, the magnitude of the fatiguing effect remains similar at both time points. Combined, our findings on CMJ and race performance (mean improvement 1.7%) align well with Ribeiro et al 30 , who demonstrated that after eight weeks of training targeted specifically for a 100 m front crawl competition, performance improved by 3.06%., with post-race decreases in measures such as peak force (16.26%) and maximal voluntary contraction force (9.33%). It is noted that 2 of our participants showed large decrements in race performance, which could potentially reflect under-training, overtraining, or even a pacing strategy adopted during the heats phase of the competition.…”
Section: Discussionsupporting
confidence: 91%
“…In the same context, Filaire et al (2001) showed that mood state increase proportionally with increasing training load. The onset of fatigue during periods of high-volume training led to decreased Vigor-activity, which negatively affects the moods of competitive athletes ( Filaire et al, 2001 ; Bachelor et al, 2023 ). The total mood disturbance and all mood state variables remains unchanged after habitual training, supporting the idea that the tapering period characterized by a decrease in training volume and training load could positively affect the psychological state of competitive swimmers.…”
Section: Discussionmentioning
confidence: 99%
“…In the same context, Filaire et al (2001) showed that mood state increase proportionally with increasing training load. The onset of fatigue during periods of high-volume training led to decreased Vigor-activity, which negatively affects the moods of competitive athletes (Filaire et al, 2001;Bachelor et al, 2023). The total mood disturbance and all Mean (SD) rating of perceived exertion (RPE) and RPE session load per week during tapering period for each group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations